Comparison of two affordable DNA extraction methods for molecular detection of Salmonella isolates from broiler farm’s boot swabs (Research, Society and Development, 2023)
There are many extraction methods available to purify bacterial DNA. PCR efficiency can vary depending on the quantity and quality of the template DNA used. This study evaluated the efficiency, quality, cost and rapidness of two in-house protocols, silica particles and Chelex-100 resin, for the extraction of twenty Salmonella isolates from boot swabs. The aim of this experiment was to compare the extraction methods for Salmonella spp. detection. DNA extraction was performed for each method and subjected to real-time PCR amplification. The amounts and integrity of DNA were determined using spectrophotometry and agarose gel electrophoresis, and the efficiency measured with real-time PCR. Limit of Detection (LOD) was determined with serial dilutions of a S. Typhimurium reference strain resulting in linear regression coefficients of R 2=0.992 (efficiency 119.31) for silica and R 2=0.958 (efficiency 93.33) for Chelex, with LOD of 10 -4 for both. Silica particles method resulted in higher DNA yield, 85.01 ± 59.11 compared to 50.74 ± 12.95 and 260/280 ratio, 1.77 ± 0.02 versus 1.63 ± 0.13. DNA integrity was superior using silica, gel showed a unique band higher than 2.000 bp, while Chelex-100 was imperceptive or degraded. Regarding PCR results, the mean quantification cycle (Cq) for silica was 17.08 ± 0.73 and Chelex-100, 17.64 ±0.56 (suggesting lower DNA values). Results showed that both methods were effective for the DNA extraction of Salmonella, once PCR resulted positive for all samples, efficiency was higher for silica. Chelex-100 resin was performed in less time at a lower cost.